READING PORTFOLIO AS A SUPPLEMENTARY ACTIVITY TO LEVERAGE STUDENTS’ READING COMPETENCY - Maulana Mualim; Feisal Aziez (BASIS (Bahasa dan Sastra Inggris), 2020)
Reading as one of the skills constructing English competency has a special portion in the curriculum of English studies programs at higher education institutions. The prevalent purpose of reading classes is to enable students to grasp knowledge from any type of text written in English. This skill could be achieved through learning a series of techniques and strategies in reading, and most importantly extensive reading activities. However, the fact that the class weights as much as 2 credits (SKS) does not give sufficient training time to achieve the maximum target. Hence, an out-of-class activity should be imposed, such as reading portfolio. This paper seeks to address the criteria of a good reading portfolio, as well as the strengths and weaknesses of this supplementary reading activity given to the students of the English Education program of IAIN Purwokerto. The data are collected through documenting the findings of previous researches on the criteria of a good reading portfolio, interviewing student-sample, and observing the process of reading portfolio given to the students of IAIN Purwokerto. The results showed that a reading portfolio should contain the purpose of the course, the text liked and picked by the students, clear scoring criteria, and continuous evaluation. The strengths of reading portfolio are evoking students’ interest for reading, instilling reading habit, and promoting learning autonomy and self-evaluation, the weaknesses are lack of resources, complex vocabulary and structure, and less motivation.